Monopolistic Competition and Costs in the Health Care Sector - Ingmar Kumpmann (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2009)
Competition among health insurers is widely considered to be a means of enhancing efficiency and containing costs in the health care system. In this paper, it is argued that this could be unsuccessful since health care providers hold a strong position on the market for health care services. Physicians exert a type of monopolistic power which can be described by Chamberlin's model of monopolistic competition. If many health insurers compete with one another, they cannot counterbalance the strong bargaining position of the physicians. Thus, health care expenditure is higher, financing either extra profits for physicians or a higher number of them. In addition, health insurers do not have an incentive to contract selectively with health care providers as long as there are no price differences between physicians. A monopolistic health insurer is able to counterbalance the strong position of physicians and to achieve lower costs. – – Wettbewerb zwischen Krankenversicherungen wird oft als Mittel zur Effizienzsteigerung und Kostendämpfung im Gesundheitswesen diskutiert. In diesem Papier wird argumentiert, dass er diese Funktion möglicherweise nicht erfüllt, wenn die Leistungserbringer auf dem Gesundheitsmarkt über Marktmacht verfügen. Ärzte besitzen einen monopolistischen Vorteil, der mit Chamberlins Modell der monopolistischen Konkurrenz dargestellt werden kann. Stehen viele Krankenversicherungen miteinander im Wettbewerb, können sie die starke Verhandlungsposition der Ärzte nicht ausgleichen. Entsprechend sind die Gesundheitsausgaben höher, womit entweder Zusatzgewinne der Ärzte oder eine größere Zahl an Ärzten finanziert werden. Außerdem haben die Krankenversicherungen keinen Anreiz zu selektivem Kontrahieren, solange es zwischen den Ärzten keine Preisunterschiede gibt. Eine MonopolKrankenversicherung kann die starke Verhandlungsposition der Ärzte ausgleichen und niedrigere Kosten durchsetzen.
urn:nbn:de:101:1-20091222743
Keywords: I11; I18; H51; D43; 330; health care system; monopolistic competition; health insurance; costs; Gesundheitswesen; monopolistische Konkurrenz; Krankenversicherung; Kosten; Gesundheitswesen; Monopolistischer Wettbewerb; Gesetzliche Krankenversicherung; Ärzte; Marktmacht; Gesundheitskosten; Theorie